Nutcases: Human rights - Spencer, Maureen (Sweet & Maxwell Limited, 2005)
Nutcases' presents the basic facts and key principles of the important cases in each area of law, in clear and straightforward language. Cases are organised by topic areas illustrating key principles of the law